Antidiabetic medications and arterial thrombotic risk reduction: a narrative review - Francesca Santilli; Paola Simeone; Rossella Liani (Internal and Emergency Medicine, 2026)
Abstract Diabetes mellitus is associated with a persistent prothrombotic state driven by platelet hyperreactivity, endothelial dysfunction, oxidative stress, and chronic low‑grade inflammation, all of which contribute to increased cardiovascular (CV) risk. Importantly, a substantial residual thrombotic risk persists even with optimal glycemic control, indicating that glucose lowering alone is insufficient to prevent vascular complications. In this context, antidiabetic therapies have emerged as important modulators of CV risk beyond their metabolic effects. Several drug classes—including metformin, thiazolidinediones, DPP‑4 inhibitors, SGLT‑2 inhibitors, and GLP‑1 receptor agonists—have been shown to influence platelet activity, endothelial function, and inflammatory pathways. These effects are mediated through mechanisms such as enhanced nitric oxide bioavailability, reduced oxidative stress, attenuation of platelet activation, and modulation of vascular inflammation. Among these, GLP‑1 receptor agonists exert particularly pronounced effects on endothelial function, oxidative stress, and platelet reactivity, alongside robust reductions in CV events. More broadly, accumulating experimental and clinical evidence indicates that several antidiabetic agents exert clinically meaningful antithrombotic actions, contributing to decreased rates of major CV events and heart failure. However, these benefits vary across drug classes and patient populations. This highlights the importance of an individualized therapeutic approach in type 2 diabetes, where treatment selection should account not only for glycemic targets but also for CV and thrombotic risk. Choosing agents with proven CV benefit may optimize overall risk reduction and improve long‑term outcomes. This narrative review aims to critically examine the available experimental and clinical evidence on the effects of antidiabetic drugs on platelet function, thrombosis, and thrombo-inflammatory pathways, highlighting the mechanisms that may contribute to cardiovascular protection beyond glucose lowering.